Quantitative methods an introduction for business management - Brandimarte, Paolo (Wiley, 2011)
"This book consists of the following four parts: Motivations and Foundations; Elementary Probability and Statistics; Decision Making Models; and Advanced Statistical Modeling. Part I is introductory, and an initial chapter provides motivation for all of the subsequent chapters by means of simple, but (hopefully) well-thought, toy examples. The following two chapters lay down necessary foundations in calculus and algebra. Part II consists of a classical course in probability and statistics, and the author stresses the use of many examples and counter-examples. Part III addresses decision making since probability and statistics are used to make decisions. Deterministic models, i.e. typical LP models, are introduced, and the emphasis is on modeling rather than computation by the simplex method. Emphasis is also placed on risk aversion and risk measures, and the author illustrates portfolio management as a main motivator. Part IV builds on Part II and discusses a few multivariate analysis models. To help less mathematically inclined readers, each chapter in Part IV contains an initial section that illustrates and motivates each approach without delving into too many details. These readers may wish to skip the remainder of each chapter. The book's companion Web site includes Microsoft Office Excel workbooks to illustrate concepts. In addition, MATLAB files, additional excercises with solutions are provided online"--